Towards earthquake resistant residential neighborhood in China : examination of vulnerability in outdoor spaces / Xue Ma and Ryuzo Ohno - Ohno, Ryuzo; Ma, Xue (Faculty of Architecture, Planning and Surveying, 2013)
China is a seismic active country. We suffered a large number of fatalities by earthquake damage. A great deal of requirements on disaster mitigation has been putting forward and which is becoming a hot topic in the society. This paper focuses on the safety situation of residential environment in Chinese cities, tries to examine the vulnerabilities for earthquake disaster mitigation. We chose the city of Tianjin as target area applying for the detail analysis. An evaluation was interpreted into suggestions and advices on planning and management.